STRATEGI PENGEMASAN PESAN DAKWAH MELALUI BAHASA VERBAL DAN NON VERBAL DALAM FILM “KURANG DUA ONS” - Nurmy Abdullah Renre; Samsul Hidayat; Meta Ratih (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2019)
Film is a universal media which can be used for various purposes, one of them is as a propaganda media as presented in the Film